SOCIAL RISKS IN THE IMPLEMENTATION OF INNOVATIVE LEARNING TECHNOLOGIES IN THE COLLEGE - D. Smolyakova (Вестник университета, 2019)
Social risks in the implementation of innovative technologies of training in college have been considered. The main directions of development of innovative changes in education have been adduced. Based on the data of sociological content analysis on this subject, the key trends of technological achievements in the educational environment of institutions of the secondary vocational education have been revealed. The concept of social risk has been given. As factors of perception of social risks its interacting components have been allocated. Based on the theory of risk society, it has been substantiated, that the risks in education are the risks of society, they are the same for the whole society and the whole Institute of education.